Crescentic glomerulonephritis in children: short-term follow-up predicts long-term outcome - Zhang, Pei; Yang, Xiao; Gao, Chun-lin; Wu, Wei; Xia, Zheng-kun (Frontiers in Pediatrics, 2023)
Background Crescentic glomerulonephritis (CrGN) is a relatively rare but severe condition in childhood with clinical feature of rapidly progressive glomerulonephritis (RPGN). The aim of this study is to investigate the clinicopathological features and prognosis of CrGN in children.We retrospectively analyzed the clinical and laboratory data, renal pathological results, treatment and outcome of 147 CrGN in two Chinese pediatric nephrology centers.Among the 147 children, there were 22 cases of type I (15.0%), 69 cases of type II (46.9%) and 56 cases of type III (38.1%). The mean percentages of crescents in CrGN I, II and III were 85.3%, 68.7% and 73.6%, respectively. Children with type I CrGN presented with more severe clinical manifestations and pathological lesions. The 3-months cumulative renal survival rates of types I, II, and III of CrGN were 66.3%, 93.6%, and 75.6%, respectively. The 1-year cumulative renal survival rates of types I, II, and III of CrGN were 56.9%, 85.3%, and 73.1%, respectively, and the 5-year cumulative renal survival rates of types I, II, and III of CrGN were 33.8%, 73.5%, and 47.1%, respectively. The Kappa Consistency Test between 3-months and 1-year total renal survival (82.1% vs 74.7%) of children was 0.683 (P < 0.001), between 1-year and 5-year total renal-free survival (78.3% vs 69.1%) of children was 0.476 (P < 0.001). The Bowman's Capsule Rupture (BCR), crescent, interstitial inflammation, and interstitial fibrosis/tubular atrophy (IF/TA)IF/TA score were predictors of end stage kidney disease (ESKD) risk, BCR showed better predictive value for ESKD than interstitial inflammation score (P=0.027) and IF/TAIF/TA score (P=0.047).Patients with type I tended to had the poorest renal survival. The three-month renal prognosis could partially reflect the 1-year renal prognosis, and 1-year mortality rate could partially reflect the 5-year mortality rate of children with CrGN.